The Important Techniques of Optimizing Interpersonal Competence in ESP Classes - Xalimovna, Maxmurova Mavjuda; Ro’ziyevna, Mirzayeva Muxayyo (International Journal on Integrated Education, 2023)
In this article the author analyses the creation of ways and techniques for the teaching of interpersonal communication skills to ESP students. The profession of the ESP student combines the challenges of interpersonal communication with the need to efficiently determine information needs of a diverse client base. The combination of skills required means that teaching these skills remains a significant challenge in training ESP class as in many other professions. The task is particularly complicated by the need for both ways and techniques to be communicated clearly and unambiguously if students are to learn effectively.